THE CORRELATION BETWEEN THE UNQUALIFIED OPINION BY THE AUDIT BOARD OF INDONESIA AND ANTI CORRUPTION ACT - Ihfan, Awaludin Nur (Faculty of Law Universitas Padjadjaran, 2023)
An Unqualified Opinion (Opini Wajar Tanpa Pengecualian) is an assessment provided by the Audit Board of Indonesia to state institutions whose financial management is deemed appropriate. However, it is often observed that entities receiving the An Unqualified Opinion designation are subsequently found to have engaged in criminal acts of corruption, which raises public doubts concerning the credibility of BPK's assessments. This study elucidates the correlation between BPK's authority to issue opinions and efforts to combat corrupt practices. The research methodology employed is juridical-normative with a legislative and case-based approach. The findings indicate that Audit Board of Indonesia plays a pivotal role in the fight against corruption. Audit Board of Indonesia 's authority to provide opinions hinges on compliance with the relevant legislation, suggesting that Audit Board of Indonesia can detect the presence or absence of criminal elements committed by the audited entities. The occurrence of corruption cases involving An Unqualified Opinion recipients is primarily due to opportunities and disclosure gaps in the audit process. A correlation exists between Audit Board of Indonesia 's opinions and anti-corruption efforts, albeit limited to the specific category of corruption related to the state's financial scope under Article 2 of Law No. 17/2003. Thus, Audit Board of Indonesia can only identify cases of corruption directly linked to the state's finances, namely Corruption Adversely Affecting State Finances under Articles 2 and 3 of Law No. 31/1999 and Embezzlement in Office under Article 8 of Law No. 20/2001.